Rhinovirus induction of fractalkine (CX3CL1) in airway and peripheral blood mononuclear cells in asthma. - Nadine Upton; David J Jackson; Alexandra A Nikonova; Suzie Hingley-Wilson; Musa Khaitov; Ajerico Del Rosario; Stephanie Traub; Maria-Belen Trujillo-Torralbo; Max Habibi; Sarah L Elkin; Onn M Kon; Michael R Edwards; et al. (PLoS ONE, 2017)
Rhinovirus infection is associated with the majority of asthma exacerbations. The role of fractalkine in anti-viral (type 1) and pathogenic (type 2) responses to rhinovirus infection in allergic asthma is unknown. To determine whether (1) fractalkine is produced in airway cells and in peripheral blood leucocytes, (2) rhinovirus infection increases production of fractalkine and (3) levels of fractalkine differ in asthmatic compared to non-asthmatic subjects. Fractalkine protein and mRNA levels were measured in bronchoalveolar lavage (BAL) cells and peripheral blood mononuclear cells (PBMCs) from non-asthmatic controls (n = 15) and mild allergic asthmatic (n = 15) subjects. Protein levels of fractalkine were also measured in macrophages polarised ex vivo to give M1 (type 1) and M2 (type 2) macrophages and in BAL fluid obtained from mild (n = 11) and moderate (n = 14) allergic asthmatic and non-asthmatic control (n = 10) subjects pre and post in vivo rhinovirus infection. BAL cells produced significantly greater levels of fractalkine than PBMCs. Rhinovirus infection increased production of fractalkine by BAL cells from non-asthmatic controls (P<0.01) and in M1-polarised macrophages (P<0.05), but not in BAL cells from mild asthmatics or in M2 polarised macrophages. Rhinovirus induced fractalkine in PBMCs from asthmatic (P<0.001) and healthy control subjects (P<0.05). Trends towards induction of fractalkine in moderate asthmatic subjects during in vivo rhinovirus infection failed to reach statistical significance. Fractalkine may be involved in both immunopathological and anti-viral immune responses to rhinovirus infection. Further investigation into how fractalkine is regulated across different cell types and into the effect of stimulation including rhinovirus infection is warranted to better understand the precise role of this unique dual adhesion factor and chemokine in immune cell recruitment.